Effects of vitamin D supplementation on ovulation and pregnancy in women with polycystic ovary syndrome: a systematic review and meta-analysis - Yang, Meina; Shen, Xiaoyang; Lu, Danhua; Peng, Jin; Zhou, Siyu; Xu, Liangzhi; Zhang, Jing (Frontiers in Endocrinology, 2023)
Objective To evaluate the effect of vitamin D supplementation on pregnancy and ovulation in patients with polycystic ovary syndrome. Method We searched Pubmed, Medline (via Ovid, 1974 to 2020), EMBASE (via Ovid, 1974 to 2020), Cochrane Central Register of Controlled Trials (via Ovid), Web of Science, CNKI, WangFang and the Vip database from inception until April 2021. Two researchers independently screened articles, collected data and evaluated the quality, with Review manager 5.3 for meta-analysis. Results Totally 20 randomized controlled studies with 1961 subjects were included. Meta analysis showed that pregnancy rate [RR=1.44 (1.28, 1.62), p<0.00,001], ovulation rate [RR=1.42 (1.14, 1.78), p=0.002] and matured oocytes rate [RR=1.08 (1.03, 1.13), p=0.002] of vitamin D supplementation group were significantly higher than those of control group. Meanwhile, early miscarriage rate [RR=0.44 (0.30, 0.66), p<0.00,001], androgen level [MD=-2.31 (-3.51, -1.11), p=0.0002], luteinizing hormone [MD=-1.47 (-2.57, -0.36), p=0.009], follicle stimulating hormone [MD=-0.15 (-0.24, -0.05), p=0.002], and premature delivery rate [RR=0.38, 95% CI (0.21, 0.70), p=0.002] were declined significantly than the controls. However, only one article suggested that the progesterone [MD=6.52 (4.52, 8.52), p<0.05] in the vitamin D intervention group was increased. There was no notable difference in the biochemical pregnancy rate [RR=0.95 (0.55, 1.63), p=0.84], gestational hypertension rate [RR=0.40, 95% CI (0.15, 1.11), p=0.08], gestational diabetes mellitus rate [RR=0.27, 95% CI (0.05, 1.39), p=0.11], fertilization rate [RR=1.05 (1.00, 1.10), p=0.04], cleavage rate [RR=1.03 (0.99, 1.06), p=0.17], high-quality embryo rate [RR=1.08 (0.98, 1.20), p=0.10], endometrial thickness [MD=0.10], 77 (-0.23, 1.77), p=0.13], estrogen level [MD=-0.34 (-1.55, 0.87), p=0.59], LH/FSH [MD=-0.14, 95% CI (-0.48, 0.20), p=1.00] and anti-Mullerian hormone [MD=-0.22 (-0.65, 0.21), p=0.32]. Conclusion Vitamin D supplementation contribute to the higher pregnancy and ovulation rates, and lower androgen, LH, FSH and early miscarriage rates in women with PCOS, regardless of the use of ovulation induction drugs or assisted reproductive technologies. However, no significant improvement was observed in fertilization rate or cleavage rate. Due to the limitation in quality of involved studies, more high-quality RCTs are needed for further validation. Systematic review registration https://www.crd.york.ac.uk/PROSPERO, identifier CRD42021250284.